Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s13550-017-0345-5
|View full text |Cite
|
Sign up to set email alerts
|

[18F]-BMS-747158-02PET imaging for evaluating hepatic mitochondrial complex 1dysfunction in a mouse model of non-alcoholic fatty liver disease

Abstract: BackgroundMitochondrial dysfunction is one of the main causes of non-alcohol fatty liver disease (NAFLD). [18F]-BMS-747158-02 (18F-BMS) which was originally developed as a myocardial perfusion imaging agent was reported to bind mitochondrial complex-1 (MC-1). The aim of this study was to investigate the potential use of 18F-BMS for evaluating hepatic MC-1 activity in mice fed a methionine- and choline-deficient (MCD) diet.Male C57BL/6J mice were fed a MCD diet for up to 2 weeks. PET scans with 18F-BMS were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…At this stage, mild steatosis and inflammation without ballooning were observed upon histopathological examination. A similar finding of early changes in hepatic mitochondrial function in mice on an MCD was recently reported using 18 F-BMS-747158-02, another PET probe for MC-I, although in that study, the diet period was only 2 weeks [ 27 ]. In that study, both liver uptake of 18 F-BMS-747158-02 and MC-I activity were measured in liver homogenate, and a high correlation was found between hepatic 18 F-BMS-747158-02 uptake and MC-I activity.…”
Section: Discussionsupporting
confidence: 80%
“…At this stage, mild steatosis and inflammation without ballooning were observed upon histopathological examination. A similar finding of early changes in hepatic mitochondrial function in mice on an MCD was recently reported using 18 F-BMS-747158-02, another PET probe for MC-I, although in that study, the diet period was only 2 weeks [ 27 ]. In that study, both liver uptake of 18 F-BMS-747158-02 and MC-I activity were measured in liver homogenate, and a high correlation was found between hepatic 18 F-BMS-747158-02 uptake and MC-I activity.…”
Section: Discussionsupporting
confidence: 80%
“…18 F-flurpiridaz ( 18 F-BMS, 18 F-BMS-747158-02) is under phase 3 clinical investigation for myocardial perfusion imaging. 18 F-flurpiridaz has shown promise in imaging mitochondria in other organs, such as liver (197), and has the potential to become an important parathyroid imaging agent (166).…”
Section: Dynamic Petmentioning
confidence: 99%
“…The University of Michigan PET Center conducted work with 11 C-labeled derivatives of rotenone in the past ( Charalambous et al, 1995a , b ; Kilbourn et al, 1997 ; Snyder et al, 1999 ), but these agents were not widely used, likely because of toxicity considerations. More recently, a pyridazinone analog, ( 18 F)BMS-747158-01 (Flurpiridaz), which advanced to clinical trials as a myocardial perfusion imaging agent ( Sattler et al, 2014 ), showed inhibitory activity for MC-1 function ( Rokugawa et al, 2017 ). Studies with the agent demonstrated high uptake and long retention not only in the heart ( Werner et al, 2019 ), but also in the brain.…”
Section: Introductionmentioning
confidence: 99%